1999
DOI: 10.1017/s1355838299982286
|View full text |Cite
|
Sign up to set email alerts
|

Transient interaction of BBP/ScSF1 and Mud2 with the splicing machinery affects the kinetics of spliceosome assembly

Abstract: Removal of introns from pre-mRNA is an essential step of gene expression. The splicing reaction is catalyzed in a large complex termed the spliceosome. Introns are recognized during the early steps of spliceosome assembly with the formation of commitment complexes. Intron recognition is mediated by the interaction of splicing factors with conserved sequences present in the pre-mRNA. BBP/SF1 participates in this recognition by interacting with the pre-mRNA branch point in both yeast and mammals. This protein, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 52 publications
8
107
0
Order By: Relevance
“…The model of invertase splicing proposes that intron 2 and intron 1 are spliced sequentially+ It was of interest, therefore, to observe that mutation of the 39 splice site of intron 1 caused mini-exon skipping+ If intron 2 removal depended on assembly of a complex between factors at the branchpoint/U-rich region and the 59 splice site, and the 39 splice site were not involved, this mutation would be expected to allow splicing of intron 2 but not subsequent splicing of intron 1+ Thus, either part of this complex simultaneously recognizes the 39 splice site or the 39 splice site is required for establishing or directing complex assembly at the branchpoint/U-rich region+ The latter suggestion is consistent with early recognition of the 39 splice site (Liu et al+, 1995)+ Protein factors that are likely to be involved in invertase mini-exon splicing are those known to interact with branchpoint, polypyrimidine tracts, or U-rich sequences+ For example, U2 auxiliary factor (U2AF) binds to vertebrate polypyrimidine tracts, and is in turn essential for binding of U2snRNP to the branchpoint sequence (Ruskin et al+, 1988)+ In general, plant introns do not contain strong polypyrimidine tracts between the branchpoint and 39 splice sites, although a preponderance of U residues often precedes the 39 splice site (Baynton et al+, 1996)+ The isolation of Arabidopsis genes encoding U2AF 65 (Domon et al+, 1998) suggests that plants contain functionally equivalent proteins+ In human and yeast, the branchpoint binding protein, BBP, binds cooperatively with U2AF 65 to the branchpoint/polypyrimidine tract (Abovich & Rosbash, 1997;Berglund et al+, 1998;Rutz & Séraphin, 1999)+ To our knowledge, a plant homolog of BBP has yet to be identified, but would be a candidate for involvement in invertase miniexon splicing+ Other factors that may be involved in establishing a complex at the branchpoint/U-rich region are plant homologs of the polypyrimidine tract binding (PTB) protein (Marin & Boronat, 1998), involved in repression of splicing in a number of alternatively spliced vertebrate systems, and plant U-rich sequence binding proteins (Gniadkowski et al+, 1996)+ Finally SR proteins have not yet been shown to bind ISEs in the vertebrate mini-exon systems, although they are clearly important in exonic enhancer systems, and hnRNP proteins are involved in both constitutive splicing and splicing of the c-src N1 mini-exon (Min et al+, 1997;Chou et al+, 1999)+ The proposed exon bridging-type reactions suggest that they may be involved in the invertase mini-exon complex+ Whether PTB, U2AF 65 , UBP-1, or other plant splicing factors, such as SR and hnRNP proteins, can affect splicing of the mini-exon is under investigation+ A number of animal intron ISEs promote splicing of heterologous exons (Carlo et al+, 1996;Modafferi & Black, 1997;Wei et al+, 1997;Cooper, 1998)+ Similarly, the signals identified in invertase intron 1 function to efficiently include the chicken cTNT mini-exon (6 nt) and inver...…”
Section: Discussionmentioning
confidence: 99%
“…The model of invertase splicing proposes that intron 2 and intron 1 are spliced sequentially+ It was of interest, therefore, to observe that mutation of the 39 splice site of intron 1 caused mini-exon skipping+ If intron 2 removal depended on assembly of a complex between factors at the branchpoint/U-rich region and the 59 splice site, and the 39 splice site were not involved, this mutation would be expected to allow splicing of intron 2 but not subsequent splicing of intron 1+ Thus, either part of this complex simultaneously recognizes the 39 splice site or the 39 splice site is required for establishing or directing complex assembly at the branchpoint/U-rich region+ The latter suggestion is consistent with early recognition of the 39 splice site (Liu et al+, 1995)+ Protein factors that are likely to be involved in invertase mini-exon splicing are those known to interact with branchpoint, polypyrimidine tracts, or U-rich sequences+ For example, U2 auxiliary factor (U2AF) binds to vertebrate polypyrimidine tracts, and is in turn essential for binding of U2snRNP to the branchpoint sequence (Ruskin et al+, 1988)+ In general, plant introns do not contain strong polypyrimidine tracts between the branchpoint and 39 splice sites, although a preponderance of U residues often precedes the 39 splice site (Baynton et al+, 1996)+ The isolation of Arabidopsis genes encoding U2AF 65 (Domon et al+, 1998) suggests that plants contain functionally equivalent proteins+ In human and yeast, the branchpoint binding protein, BBP, binds cooperatively with U2AF 65 to the branchpoint/polypyrimidine tract (Abovich & Rosbash, 1997;Berglund et al+, 1998;Rutz & Séraphin, 1999)+ To our knowledge, a plant homolog of BBP has yet to be identified, but would be a candidate for involvement in invertase miniexon splicing+ Other factors that may be involved in establishing a complex at the branchpoint/U-rich region are plant homologs of the polypyrimidine tract binding (PTB) protein (Marin & Boronat, 1998), involved in repression of splicing in a number of alternatively spliced vertebrate systems, and plant U-rich sequence binding proteins (Gniadkowski et al+, 1996)+ Finally SR proteins have not yet been shown to bind ISEs in the vertebrate mini-exon systems, although they are clearly important in exonic enhancer systems, and hnRNP proteins are involved in both constitutive splicing and splicing of the c-src N1 mini-exon (Min et al+, 1997;Chou et al+, 1999)+ The proposed exon bridging-type reactions suggest that they may be involved in the invertase mini-exon complex+ Whether PTB, U2AF 65 , UBP-1, or other plant splicing factors, such as SR and hnRNP proteins, can affect splicing of the mini-exon is under investigation+ A number of animal intron ISEs promote splicing of heterologous exons (Carlo et al+, 1996;Modafferi & Black, 1997;Wei et al+, 1997;Cooper, 1998)+ Similarly, the signals identified in invertase intron 1 function to efficiently include the chicken cTNT mini-exon (6 nt) and inver...…”
Section: Discussionmentioning
confidence: 99%
“…Saccharomyces cerevisiae Msl5 (branchpoint binding protein) orchestrates spliceosome assembly by binding the intron branchpoint sequence 59-UACUAAC and establishing cross intron-bridging interactions with other components of the splicing machinery (Abovich et al 1994;Abovich and Rosbash 1997;Rain et al 1998;Rutz and Seraphin 1999;Wang et al 2008;Chang et al 2012). Unlike the optional splicing factors discussed above, Msl5 (a 476-aa polypeptide) is essential for yeast vegetative growth.…”
Section: Synthetic Genetic Interactions Of Cbc2-y24a With the Yeast Bmentioning
confidence: 99%
“…Nam8 and Mud1 are components of the U1 snRNP. Mud2 interacts with the pre-mRNA/U1snRNP commitment complex, in a manner that depends on the branchpoint sequence of the intron and the association of Mud2 with the yeast branchpoint binding protein (BBP), and then facilitates recruitment of the U2 snRNP (Abovich et al 1994;Abovich and Rosbash 1997;Rain et al 1998;Rutz and Seraphin 1999;Wang et al 2008). Mud2 and Mud1 appear to be functionally overlapping, insofar as the mud1D mud2D double mutation is lethal (Abovich et al 1994).…”
Section: Introductionmentioning
confidence: 99%